Formulation and preclinical evaluation of a Toll-like receptor 7/8 agonist as an anti-tumoral immunomodulator - Lu, Ruolin (J Control Release, 2019)
The toll-like receptor 7 and 8 (TLR7/8) agonist Resiquimod (R848) has been recognized as a promising immunostimulator for the treatment of cutaneous cancers in multiple clinical trials. However, systemic administration of R848 often results in strong immune-related toxicities while having limited therapeutic effects to the tumor. In the present study, a prodrug-based nanocarrier delivery system was developed that exhibited high therapeutic efficiency. R848 was conjugated to α-tocopherol to constitute an R848-Toco prodrug, followed by formulating with a tocopherol-modified hyaluronic acid (HA-Toco) as a polymeric nano-suspension. In vitro evaluation showed that the delivery system prolonged the release kinetics while maintaining TLR agonist activities. When administered subcutaneously, the nano-suspension formed a depot at the injection site, inducing localized immune responses without systemic expansion. This formulation also suppressed tumor growth and recruited immune cells to the tumor in a murine model of head and neck cancer. In a pilot canine clinical trial of spontaneous mast cell tumors, the treatment led to a 67% response rate (3 partial remissions and 1 complete remission).